Ambiente de simulación sobre señales, sistemas y control dinámico en dispositivos móviles. - García Vega, Andres Felipe (Universidad Antonio Nariño, 2022)
This Integral Degree Project (TIG) is part of a modular project of Fundación Conciencia Activa, which aims to develop an application for mobile devices using the Python open source Kivy framework . The main reason for its development is to provide electronic engineering students with the possibility of consolidating and expanding their knowledge through this study environment tool. Its mobile execution was taken into account because most of the students have a functional and compatible phone